Hyperventilation in Adult TBI Patients: How to Approach It? - Gouvea Bogossian, Elisa; Peluso, Lorenzo; Creteur, Jacques; Taccone, Fabio Silvio (Frontiers in Neurology, 2021)
Hyperventilation is a commonly used therapy to treat intracranial hypertension (ICTH) in traumatic brain injury patients (TBI). Hyperventilation promotes hypocapnia, which causes vasoconstriction in the cerebral arterioles and thus reduces cerebral blood flow and, to a lesser extent, cerebral blood volume effectively, decreasing temporarily intracranial pressure. However, hyperventilation can have serious systemic and cerebral deleterious effects, such as ventilator-induced lung injury or cerebral ischemia. The routine use of this therapy is therefore not recommended. Conversely, in specific conditions, such as refractory ICHT and imminent brain herniation, it can be an effective life-saving rescue therapy. The aim of this review is to describe the impact of hyperventilation on extra-cerebral organs and cerebral hemodynamics or metabolism, as well as to discuss the side effects and how to implement it to manage TBI patients.